WESTERNISASI, PERUBAHAN BUDAYA DAN MORAL: PERAN PENDIDIKAN PANCASILA DALAM KEHIDUPAN MAHASISWA - Simanjuntak, Zireh Kharisma (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Westernization has exerted a significant influence on the culture and morality of Indonesian university students, particularly in the era of rapid globalization and easy access to information. This phenomenon has led to changes in lifestyle, behaviour, and mindset among students, often conflicting with the foundational values of Pancasila as the nation's guiding philosophy. This study aims to analyse the impact of westernization on cultural and moral shifts among students, while highlighting the critical role of Pancasila Education in reinforcing national identity and moral character. Employing a descriptive qualitative approach based on literature analysis, the study finds that inadequate cultural filtering can weaken the implementation of Pancasila and trigger a moral crisis within the student community. Pancasila Education is shown to be essential in instilling core national values, shaping character, and preventing the infiltration of foreign ideologies that contradict Indonesia’s identity. Strengthening Pancasila Education within academic environments is therefore a key strategy in cultivating a generation of students who are culturally grounded, morally responsible, and capable of serving as positive agents of change amid the currents of globalization.